MARS WEATHER MONITORING ROBOTIC SYSTEM USING ROCKER BOGIE MECHANISM (International Journal of Food and Nutritional Sciences, 2022)
The exploration of Mars has been a subject of immense scientific interest, prompting the development of advanced robotic systems capable of traversing the challenging Martian terrain. The Rocker Bogie mechanism has emerged as a reliable and efficient mobility system for Mars rovers, allowing them to navigate over rough and uneven surfaces with enhanced stability and manoeuvrability. This paper presents, Mars Weather Monitoring Robotic System using Rocker Bogie Mechanism. The proposed Mars robot employs a six-wheeled configuration with a Rocker Bogie suspension system, enabling the robot to maintain stability while traversing obstacles and uneven terrain. The robot's ability to negotiate obstacles, climb slopes, and traverse loose or rocky surfaces is assessed, providing insights into its operational capabilities and limitations. The robot will be equipped with cameras, spectrometers, and other scientific instruments to analyze the Martian environment and gather valuable data for further exploration and research. The objective of this project is to examine the temperature, humidity and water molecules on the surface of the mars and to send the observations to the operators.